2019
DOI: 10.1108/mrjiam-11-2018-0876
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge-intensive entrepreneurship: a systematic review and future directions

Abstract: Purpose This study aims to propose a framework based on the main theoretical and empirical contributions present in the literature and articulate the main paths for future studies in knowledge-intensive entrepreneurship (KIE). Design/methodology/approach Using the systematic review method from a survey of 85 articles, related to the KIE focal issue, originated from the Web of Science, it was possible to exhaustively analyze the studies and to divide the theme into key categories. Findings The present resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 75 publications
(82 reference statements)
1
4
0
2
Order By: Relevance
“…The complete empirical model (Figure 2) allows us to confirm that a knowledge ecosystem positively affects ecosystem dynamics in KIE, which is coherent with the literature (Abualbasal & Badran, 2019;Isaksen & Trippl, 2017;Malerba & McKelvey, 2020;Morris, Shirokova, & Tsukanova, 2017;Spigel, 2017;Stam, 2009). In addition, it is confirmed that the socioeconomic dimension impacts the ecosystem dynamics, where the geographic and regional characteristics impact KIE, allowing a local intensification of initiatives as well as considering local and economic issues, as is the case of São Paulo (Fischer, Schaeffer, & Silveira, 2018;Sousa & Silva, 2019). This result also has theoretical and empirical support from previous assessments (Crescenzi & Rodríguez-Pose, 2012;Radosevic & Yoruk, 2013;Strumsky & Thill, 2013).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The complete empirical model (Figure 2) allows us to confirm that a knowledge ecosystem positively affects ecosystem dynamics in KIE, which is coherent with the literature (Abualbasal & Badran, 2019;Isaksen & Trippl, 2017;Malerba & McKelvey, 2020;Morris, Shirokova, & Tsukanova, 2017;Spigel, 2017;Stam, 2009). In addition, it is confirmed that the socioeconomic dimension impacts the ecosystem dynamics, where the geographic and regional characteristics impact KIE, allowing a local intensification of initiatives as well as considering local and economic issues, as is the case of São Paulo (Fischer, Schaeffer, & Silveira, 2018;Sousa & Silva, 2019). This result also has theoretical and empirical support from previous assessments (Crescenzi & Rodríguez-Pose, 2012;Radosevic & Yoruk, 2013;Strumsky & Thill, 2013).…”
Section: Discussionsupporting
confidence: 85%
“…The research used classification information from PIPE projects to classify companies as green or traditional KIE. Traditional KIE is taken as the socioeconomic phenomenon that drives aggregate economic competitiveness and innovative capabilities by intensively using knowledge Sousa & Silva, 2019;Malerba & Mckelvey, 2020), while green KIE is understood as the initiatives that identify, evaluate, and process opportunities with a commitment to sustainability and environmental compatibility (Lotfi, Yousefi, & Jafari, 2018;Ye, Zhou, Anwar, Siddiquei, & Asmi, 2020). Project information is public and available on the Fapesp website (summary, description, location, knowledge area, keywords, direct and indirect impacts).…”
Section: Methodological Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…By developing a particular SSS model for IKN financing, the Government can form an SSS tailored to infrastructure development in this area. The four methods (Kirby & Worner, 2014;Soares da Silva et al, 2019) can be applied simultaneously. In the context of SSS objectives, for example, when selling shares, a clear objective must be explained to the community to finance infrastructure projects and collaborative efforts with other institutions to encourage direct community participation.…”
Section: Development Of Economic Supporting Infrastructure In the Nat...mentioning
confidence: 99%
“…Clustering theory, as summarized in this paper, explores the spatial concentration of high-tech industries and the benefits of agglomeration [11][12][13][14][15][16][17][18][19][20]. Studies on innovation ecosystems analyze interactions among firms, universities, research institutions, and government agencies with a focus on knowledge exchange and technology transfer [21][22][23][24][25][26]. Policymakers need to comprehend the specific challenges within developing entrepreneurial ecosystems and formulate policies adapted to the local context [27].…”
Section: Research Theory Reviewmentioning
confidence: 99%